Analisis Tata Kelola Tambang di Kabupaten Padang Pariaman Provinsi Sumatera Barat - Putri, Dewi Zaini; Adry, Melti Roza; Hernanda, Tiara Aprilia Putri (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
The high demand for sand as a result of urbanization, population growth, increased demand for housing and infrastructure development causes excessive sand exploitation, which can have a negative impact on the environment due to weak mining governance. This study aims to analyze the impact and mining activities on social, economic and environmental conditions in Padang Pariaman Regency. In addition, it also analyzes the management of sand, stone and gravel mining in Padang Pariaman Regency. This research was conducted in Padang Pariaman Regency, West Sumatra Province. The data in this study used secondary data obtained from BPS and primary data related to mining governance in Padang Pariaman District obtained through in-depth interviews with nagari and community officials. The results showed that the output of the mining and quarrying sector had a good impact on social, economic variables, but had a negative impact on the environment in the mining area. This indicates that the concept of sustainable development has not been achieved in the study area. Therefore, the importance of mining governance and collaboration between actors both local communities, nagari officials, local governments and private parties involved in sand, stone and gravel mining business in Padang Pariaman Regency.